Corporate Social Responsibility (CSR) of Innovative Pharmaceutical Corporations. The Case of BIOGEN - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2018)
The aim of this paper is to discuss the common features and specificity of Corporate Social Responsibility (CSR) practices of innovative transnational corporations (TNCs) acting in the pharmaceutical industry. The innovativeness of pharmaceutical firms is understood here as their ability to make a breakthrough in the treatment of rare, incurable diseases. The examination of the issue leads to the conclusion that the specificity of CSR in this industry is related to the contradiction between the economic and social/ethical aspects of innovation processes in this field. A key issue of CSR in the innovative pharmaceutical industry seems to be the pricing of drugs, especially orphan and ultra-orphan drugs, resulting in patients from less developed countries having limited access to life-saving medicines or those that improve the quality of life. Corporations use their monopolistic position to set extremely high prices. However, without the market/marketing exclusivity offered to pharmaceutical firms by the law, orphan drugs would probably not be developed, produced and commercialized. Traditional CSR practices (corporate philanthropy, community and neighborhood programs, volunteerism etc.) cannot be treated as sufficient "compensation" for the high prices of medicines. Real, true CSR in the innovative pharmaceutical industry requires either abandoning or reducing extreme monopolistic privileges and offering medicines for rare diseases at lower prices.
Keywords: M14; L65; 330; Corporate Social Responsibility (CSR); innovative pharmaceutical corporations; orphan drugs; access to drugs; BIOGEN